Analyzing value creation in electronic retailing: The case of Digikala–Part A. Issue 2 (November 2020) - Hanafizadeh, Payam; Mehri, Saeedeh; Hasanabadi, Hamid
Many e-commerce businesses are emerging in the form of start-ups in Iran. Plenty of these businesses fail to gain significant market share. Electronic retail stores are among the most commonly used electronic business models. Despite the many challenges facing e-retailers due to market changes and customer preferences, Digikala has been ranked as the most popular and most visited website and has managed to gain over 85% of the Iranian retail market. In addition, Digikala is one of the largest electronic retailers in the Middle East. This study aims at analyzing value creation in Digikala in order to overcome these challenges and answering the following question: What value does Digikala create?